Surfactant free gram scale synthesis of mesoporous Ni(OH)(2)-r-GO nanocomposite for high rate pseudocapacitor application - Singh, Upendra; Banerjee, Abhik; Mhamane, Dattakumar; Suryawanshi, Anil; Upadhyay, Kush Kumar; Ogale, Satishchandra (RSC Advances, 2014)
We report a single-step surfactant-free gram scale hydrothermal synthesis of mesoporous Ni(OH)(2) nanoparticles and the Ni(OH)(2)-reduced graphene oxide (Ni(OH)(2)-r-GO) nanocomposite. Interesting morphological features are noted. These nanomaterials are examined and compared as cathode materials for pseudo-capacitor application through detailed characterizations. A high specific capacitance (C-s) of 1538 F g(-1) is observed for Ni(OH)(2)-r-GO even at a high current density of 40 A g(-1), whereas at the same current rate, bare Ni(OH)(2) shows C-s of only 936 F g(-1).